If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16(x + 3) = 7(x + -5) + -9(x + 4) + -7 Reorder the terms: 16(3 + x) = 7(x + -5) + -9(x + 4) + -7 (3 * 16 + x * 16) = 7(x + -5) + -9(x + 4) + -7 (48 + 16x) = 7(x + -5) + -9(x + 4) + -7 Reorder the terms: 48 + 16x = 7(-5 + x) + -9(x + 4) + -7 48 + 16x = (-5 * 7 + x * 7) + -9(x + 4) + -7 48 + 16x = (-35 + 7x) + -9(x + 4) + -7 Reorder the terms: 48 + 16x = -35 + 7x + -9(4 + x) + -7 48 + 16x = -35 + 7x + (4 * -9 + x * -9) + -7 48 + 16x = -35 + 7x + (-36 + -9x) + -7 Reorder the terms: 48 + 16x = -35 + -36 + -7 + 7x + -9x Combine like terms: -35 + -36 = -71 48 + 16x = -71 + -7 + 7x + -9x Combine like terms: -71 + -7 = -78 48 + 16x = -78 + 7x + -9x Combine like terms: 7x + -9x = -2x 48 + 16x = -78 + -2x Solving 48 + 16x = -78 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 48 + 16x + 2x = -78 + -2x + 2x Combine like terms: 16x + 2x = 18x 48 + 18x = -78 + -2x + 2x Combine like terms: -2x + 2x = 0 48 + 18x = -78 + 0 48 + 18x = -78 Add '-48' to each side of the equation. 48 + -48 + 18x = -78 + -48 Combine like terms: 48 + -48 = 0 0 + 18x = -78 + -48 18x = -78 + -48 Combine like terms: -78 + -48 = -126 18x = -126 Divide each side by '18'. x = -7 Simplifying x = -7
| 6x^2-48x=36 | | 11a^3-11a= | | -32x=34x-x+1 | | 3x^2*18x+37=0 | | ny+mx=c | | x^2+20x-78=0 | | -4=6x-10x | | p=2.50(200)-500 | | 5x^2-180= | | 2[5x-10]+17=37 | | -3x^2+10x+8=0 | | X-x+6=2(x+3) | | 2(x-1.5)=2x-3 | | 12y=3+x | | -2(3x-5)=-110 | | 60x=30x+40x | | -2(3x-5)=-10 | | 56x+127=21 | | 2x-22=54 | | H=-16t^2+30t+78 | | 8x=2x-10x | | X=x-7 | | 32x^2y-2y=0 | | 16s^2-100=0 | | 12x^4+30x^3+12x^2=0 | | -8x=2x-10x | | 5x^2-65x-10=0 | | 5(x+2)=2x+3x+10 | | 2x^2z+20xz+32z=0 | | 7x^2-49x+84=0 | | 2x^2+2y^2-16x+12y+50=0 | | 9n+5n= |